Analysis of Implementation of Reputation Risk Management in Employees of Sharia Bank (Case Study of Bank Sumut Sub-Branch Office Sharia Simpang Kayu Besar Tanjung Morawa) - Simanjuntak, Wiwin Khairany; Lathief Ilhamy Nasution, Muhammad; Jannah, Nurul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The future of banking is largely determined by the management capabilities of Islamic banking and facing the rapid changes that are happening at this time. The rapid pace of information and technology as well as financial innovation has made the financial sector where Islamic banking takes shelter increasingly complex, dynamic, and competitive. This condition has the potential to increase risks to Islamic banking where all these risks absolutely must be managed. Islamic banks should start to manage such risks as reputation risk, for example. Reputation risk is the risk due to decreased stakeholder trust originating from negative perceptions of the bank. The impact of reputation risk events generally causes non-financial losses for the bank. The purpose of this study was to determine the analysis of the implementation of reputation risk management of Islamic banks on employees. The research method of this journal is a descriptive qualitative method with a case study approach from the data using collected three methods, namely, direct interview observation, and documentation. The results of the study show that the role of implementing risk management in North Sumatra companies or banks is very important because in reputation risk there must be control in the company by increasing compliance with applicable regulations in order to control reputation risk. Companies must also anticipate complaints from customers and lawsuits.